PROBLEMATIKA SLOW LEARNER - Nana Suryana (Latifah Pres, 2018)
In the learning process, teachers will face a variety of differences that children have, for example children who are slow to follow learning. A slow learner is not a stupid child. Children of slow learners are only delays in following the teaching and learning process compared to other children. This is caused by wrong perceptions of children, emotional disturbances, and errors in education.